Implementation of the Glasser Model with the Help of Animation Media Based on Local Wisdom to Improve the Writing Skills of Uhnp Indonesian Language Education Program Students - Marlina Agkris Tambunan; Jumaria Sirait; Immanuel Silitonga (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research was prepared with the aim of improving the writing skills of students in the Indonesian Language Education Study Program, UHNP using the Glasser model with the help of animation media based on local wisdom. This type of research is Classroom Action Research (PTK), where the teacher is the implementer of the learning while the researcher is the observer. This research design uses the Kemmis and Mc model. Taggart. This research was carried out in the even semester of the 2023/2024 academic year, namely in March. The subjects of this research were students from the Indonesian language education study program, consisting of 20 students. The object of research is students' writing skills. Data collection techniques use tests and observation. Data were analyzed descriptively and presented in table form. The results of the research showed that there was an increase in students' writing skills, the average writing skills score in the first cycle of the first meeting was 65.45 and the second meeting was 68.05. In cycle II the average value of speaking skills for the first meeting was 70.65 and for the second meeting was 89.5. This means that improving learning outcomes by using the glasser model with the help of animation media based on local wisdom can improve the skills of students in the Indonesian Language Education Study Program.